Sure success in ophthalmology : viva voce & practical examination - Datta, Jyotirmoy; Boyd L., Samuel; Drews, Robert C. (New Delhi : Jaypee Brothers Medical Publishers, 2013)
El libro está bien ilustrado para comprender los conceptos básicos de oftalmología. Cubre casi todas las preguntas probables junto con las respuestas que generalmente se solicitan en el examen MBBS.
The book is well illustrated for unders-tanding basics of ophthalmology. It almost covers all probable questions along with answers which are usually asked in MBBS examination.
CONTENTS 1. History taking and examination of an ophthalmic case 2. Eyelid 3. Conjunctiva and sclera 4. Cornea 5. Lens y otros 12 capítulos más
Keywords: ENFERMEDADES DE LA RETINA; OFTALMOLOGÍA; OPHTHALMOLOGY